Spanish Jew or Hispanist? Abraham Z. López-Penha and the negotiation of Columbian, Pan-Hispanic, and Sephardic identity. Issue 4 (2nd October 2019) - Allard, Elisabeth Bolorinos
ABSTRACT: This article explores the negotiation of Sephardic, Columbian, and Hispanic identity in the writing and correspondence of Abraham Zacharías López-Penha (1865–1927), a Colombian writer of Sephardic Jewish Curaçaoan origin. Focusing on his most acclaimed work, El libro de las incoherencias (1909), it questions why, as a Columbian writer, López-Penha chooses to identify himself as a 'Spanish Jew', particularly in the context of his relationship with the founder of Spanish Philosephardism, Angel Pulido. It also questions how López-Penha's Sephardic identity fits within the discourse of Spanish-American hispanism, particularly its racial parameters.